2019
DOI: 10.1016/j.nucengdes.2019.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local damage to reinforced concrete panels subjected to oblique impact by soft missile

Abstract: Many empirical formulas have been proposed for evaluating local damage to reinforced concrete structures caused by impacts of rigid missiles. Most of these formulas have been derived based on tests involving impact perpendicular to target structures. Thus far, few tests with oblique impact onto target structures have been carried out. In this study, we aim to propose a new formula for evaluating the local damage caused by oblique impact based on previous experimental and simulation results. In this study, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Based on our previous work (Nishida et al, 2018(Nishida et al, , 2019, the proposed analytical method in terms of calibration analysis was validated by compared with the experimental results derived from the aforementioned small-scale impact tests (Fig. 2).…”
Section: Comparison Of Experimental and Analytical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous work (Nishida et al, 2018(Nishida et al, , 2019, the proposed analytical method in terms of calibration analysis was validated by compared with the experimental results derived from the aforementioned small-scale impact tests (Fig. 2).…”
Section: Comparison Of Experimental and Analytical Resultsmentioning
confidence: 99%
“…The target RC slab used in this simulation analysis is the same as the reference (Nishida et al, 2019) shown in Fig. 4.…”
Section: Finite Element Modeling 321 Rc Slabmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the impact force-time history measured in the experiment is in good agreement with that calculated using the modified Riera model. The finite element code LS-DYNA with Lagrange finite elements and explicit time integration was used, by Nishida et al [27], to study the damage of reinforced concrete subjected to oblique impact by soft missile at various impact velocities and angles. The material model of the concrete employed in the simulation analyses was the Winfrith model (MAT #084) installed in LS-DYNA.…”
Section: Introductionmentioning
confidence: 99%